PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN ECOPRENEURSHIP DAN MANAJEMEN PENGELOLAAN SAMPAH - Purwidianti, Wida; Dwiyanti, Retno; Ma’ruf, Anwar; Elora Fitri Solihfahmi, Tsabitah; Nur Hamam, Zaki (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2025)
Green entrepreneurship (ecopreneurship) is entrepreneurship that does not only focus on profit but also pays attention to environmental aspects. One form of green entrepreneurship is by managing waste into a business that generates profits and preserves the environment. This community service (IbM) conducts training on ecopreneurship and waste management with partners of Rumah Asuh Baiti Jannati in Purwokerto. The purpose of this IbM is to overcome partner problems related to the lack of funding to finance the children of this foster home. The IbM activity was carried out on May 18, 2025 at Rumah Asuh Baiti Jannati. The activities carried out were in the form of providing material on ecopreneurship and entrepreneurial motivation as well as waste management training. This activity has proven effective based on the results of the pretest and posttest which showed an increase in the knowledge of community service participants and an increase in the skills of partners in managing inorganic waste into compost. This activity was also considered very good by partners based on the results of the partner satisfaction survey